Evaluasi Penerapan Peraturan Mahkamah Agung Republik Indonesia Nomor 1 Tahun 2020 Tentang Pedoman Pemidanaan Pasal 2 dan Pasal 3 Undang-Undang Pemberantasan Tindak Pidana Korupsi: Disparitas Putusan dalam Pengadilan Tindak Pidana Korupsi di Pengadilan Negeri Medan - puteh, ibrahim; Chaniago, Hidayat (Jurnal Transformasi Administrasi, 2023)
The disparity of decisions in corruption trials has become a significant issue in the Medan District Court. The purpose of this study is to examine and analyze the factors that cause disparities in decisions in cases of corruption in that court. The research method used is a qualitative approach by collecting data through interviews with judges, prosecutors and lawyers involved in corruption cases. The results of the study indicate that there are several factors that contribute to the disparity of decisions in the Medan District Court. These factors include subjective interpretation of facts and law, judges' knowledge and awareness of existing guidelines, limited resources, and the quality of evidence and various investigative processes. The disparity of decisions in trials of corruption can threaten justice and public trust in the justice system. Therefore, efforts are needed to overcome this disparity. Recommendations resulting from this research include more intensive training and education for judges, increased coordination and collaboration between stakeholders, allocation of adequate resources, and regular evaluation of the implementation of existing guidelines. This research is expected to provide a more in-depth understanding of the problem of decision disparity in corruption trials at the Medan District Court. Through this understanding, it is hoped that corrective steps can be taken to achieve harmonization of decisions and ensure justice that is in line with legal objectives and the interests of society.